Diagnosis and treatment of cerebral vasospasm after subarachnoid hemorrhage - Youssef Fardos; Daniel Mattimore; Wesam Andraous; Sofia Geralemou; Sergio Bergese; Ana Costa (Academia Biology)
Cerebral vasospasm after subarachnoid hemorrhage leads to delayed cerebral ischemia and contributes to increased morbidity and mortality. Stroke secondary to vasospasm accounts for almost half of the early deaths after subarachnoid hemorrhage. The timely diagnosis of vasospasm is paramount in the implementation of treatment modalities. A few diagnostic tools serve to detect cerebral vasospasm with varying degrees of accuracy and potential complications. Digital subtraction angiography remains the gold standard test for the diagnosis of cerebral vasospasm as it allows for a quantitative assessment of vasospasm in each intracranial artery as well as therapeutic interventions. Due to the delayed occurrence of vasospasm following subarachnoid hemorrhage, preventive therapies have drawn significant interest in addressing different stages of their development. If vasospasm is suspected, treatment consists of hemodynamic augmentation, drug therapy, and minimally invasive.